The Development of HOTS Instruments In Biology Learning - Santosa, Tomi Apra; Festiyed, Festiyed; Zulyusri, Zulyusri; Razak, Abdul (Universitas Wiralodra, 2023)
This study aims to produce valid and reliable Higher Order Thinking Skills instruments in learning the biology of ecology and environment material. The research is a Research and Development study with the ADDIE model. The research was conducted at SMA Negeri Kerinci. The sample in the study came from 2 biology education lecturers and 3 biology teachers. The instruments in this study were a 20-item multiple-choice HOTS test sheet and a validation questionnaire. Data collection techniques are tests and validation questionnaires. Indicators of Higher Order Thinking Skills are the ability to analyze, evaluate and create. Data analysis is quantitative and qualitative data analysis with the help of the SPSS version 16 application. The results showed that the Higher Order Thinking Skills instrument had a validation value of 0.724 with decent criteria and reliability of 0.972 with high criteria. These findings explain that the Higher Order Thinking SSkills(HOTS) instrument is very valid and reliable for use in ecology and environmental materials.